Robust Biocompatible Fibers from Silk Fibroin Coated MXene Sheets (Adv. Mater. Interfaces 9/2023). Issue 9 (24th March 2023) - Usman, Ken Aldren S.; Yao, Ya; Bacal, Christine Jurene O.; Zhang, Jizhen; Jarvis, Karyn L.; Lynch, Peter A.; Mota‐Santiago, Pablo; Qin, Si; Naebe, Minoo; Henderson, Luke C.; Hegh, Dylan Y.; Allardyce, Benjamin J.; et al.
Abstract : Robust Biocompatible MXene Composite Fibers In article number 2201634, Ken Aldren S. Usman, Joselito M. Razal, and co‐workers report a strategy of fabricating robust and delamination resistant MXene composite fibers by introducing small amounts of silk fibroins into their wet‐spinning formulations. These fibers exhibit delamination resistance under agitation forces such as ultrasonication, and conductivity retention upon prolonged storage in simulated physiological conditions. Subsequent biocompatibility tests also revealed their potential use in flexible electronics and biomedical applications.